2019
DOI: 10.2478/ijafr-2019-0004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of QoI resistance and mtDNA diversity in the Irish Zymoseptoria tritici population

Abstract: The emergence and spread of Quinone outside Inhibitor (QoI) fungicide resistance in the Irish Zymoseptoria tritici population in the early 2000s had immediate impacts on the efficacy of the entire group of fungicides for the control of septoria tritici blotch. As a result, a dramatic reduction in the quantities applied to winter wheat occurred in the following seasons. Even in the absence of these fungicides, the frequency of the resistance allele, G143A in the pathogens mtDNA has remained exceptionally high (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…The conformity of the two marker sets demonstrates that the housekeeping gene markers, like SSR markers, are neutral and unlinked to the genes involved in fungicide resistance. The lack of population structure among the three Irish fields agree with previous studies, where little geographic differentiation among Z. tritici populations was found within Ireland (Welch et al, 2018;Kildea et al, 2019a) as well as on a wider geographic scale (Zhan et al, 2003;McDonald and Mundt, 2016) and is suggested to be explained by high gene flow between populations combined with regular sexual recombination. The differences observed in patterns of fungicide sensitivity and haplotype distribution of fungicide resistance genes among locations, despite the high similarity for neutral markers, suggest that the rate of gene flow may not be sufficient to counteract gene frequency changes caused by ongoing local selection for fungicide resistance.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The conformity of the two marker sets demonstrates that the housekeeping gene markers, like SSR markers, are neutral and unlinked to the genes involved in fungicide resistance. The lack of population structure among the three Irish fields agree with previous studies, where little geographic differentiation among Z. tritici populations was found within Ireland (Welch et al, 2018;Kildea et al, 2019a) as well as on a wider geographic scale (Zhan et al, 2003;McDonald and Mundt, 2016) and is suggested to be explained by high gene flow between populations combined with regular sexual recombination. The differences observed in patterns of fungicide sensitivity and haplotype distribution of fungicide resistance genes among locations, despite the high similarity for neutral markers, suggest that the rate of gene flow may not be sufficient to counteract gene frequency changes caused by ongoing local selection for fungicide resistance.…”
Section: Discussionsupporting
confidence: 90%
“…The number of isolates sequenced varies for the different target genes. d PCR-RFLP used for the detection of the cytochrome b substitution G143A as reported by Kildea et al (2019a). e Sensitivity as determined using in vitro microtitre plate assays as described by Dooley et al (2016b).…”
Section: Pacbio Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the management of STB, fungicides are generally used. However, fungicide resistance has been oftenly reported (Hayes et al, 2016;Kettles and Kanyuka, 2016;Kildea et al, 2019). Because, STB may overcome fungicides through its genetic variability.…”
Section: Discussionmentioning
confidence: 99%
“…During the last few years, the frequencies of the CYP51 mutations V136C, A379G, and I381V have been relatively stable across Europe, while a clear pattern of decreasing frequencies of D134G, V136A, and S524T from west to east has been observed [ 4 ]. Due to the continuous accumulation of mutations, a reduction in the field efficacy of tebuconazole, epoxiconazole, and also prothioconazole has been observed in many European countries during the last few years [ 4 , 20 , 21 , 22 , 23 ]. The decline in the efficacy of azoles has started to accelerate, probably due to the appearance of mutation S524T in Zt’s field populations [ 4 , 15 ].…”
Section: Introductionmentioning
confidence: 99%